PENGARUH FASILITAS DAN KUALITAS PELAYANAN TERHADAP KEPUASAN WISATAWAN (Studi Kasus Pada Wisata Pantai Tanjung Pakis Karawang) - Tiara Sobari; Danny Ramdhani (Jurnal Mirai Management, 2021)
This study aims to determine the effect of Facilities and Service Quality on Tourist Satisfaction (Case Study on Tanjung Pakis Beach Tourism). The research method used is descriptive verification with a quantitative approach, with the data sources used are primary data and secondary data. The research sample was 400 visitors who were traveling on Tanjung Pakis Beach, using the slovin method. The analysis used is multiple regression analysis and hypothesis testing using t test and F test with the help of SPSS version 25. The results show that facilities based on respondents' perceptions have an achievement score of 8,922 or 64.9% of the ideal score, Service Quality has an achievement score 9,076 or 62.5% of the ideal score, and Tourist Satisfaction has an achievement score of 9,204 or 65.5% of the ideal score. The results of the correlation hypothesis test between Facilities and Service Quality have a strong and unidirectional relationship level, Facilities partially have a positive and significant influence on Tourist Satisfaction, Service Quality has a positive and significant influence on Tourist Satisfaction and the results of the hypothesis that Facilities and Service Quality simultaneously have a positive influence and significant to Tourist Satisfaction. The results of the r2 test for Facilities and Service Quality on Tourist Satisfaction obtained an R² value of 0.711 or 71.1%, meaning that Tourist Satisfaction is influenced by the two independent variables of 71.1%, while 28.9% is influenced by other variables not examined in this study. Keywords: Facilities_1, Service Quality_1 ,Tourist Satisfaction_3